Processo criativo na performance percussiva contemporânea: articulações entre pesquisa, gesto cênico e mediação tecnológica - Alves, Carlos Henrique de Morais (2017)
This work is an artistic research on the creative process in contemporary percussive performance. Through theoretical and practical investigation, we seek to problematize and develop questions about interpretation in a dialogue with: mixed-technique notation, corporality and open-form experimental music, illustrated here by the preparation of two solo percussion pieces: ?Corporel for body percussion, and Science Fiction Sceneries for percussion, electronics and video. Through research in music performance, we present a way for planning and executing these pieces through artistic research, performance musicology and morphology of the open work. From the planning of ?Corporel, we proposed a characterization of the body in a theatrical perspective. The methodology consisted in developing experimentation workshops where we describe the process of planning and the activities oriented by a scene director. In Science Fiction Sceneries, we reproduce the details of the process of collaboration between composer and performer, by developing a performance script. In this work, composed for the dissertation, the focus is on real-time interaction with the video. We show specifically how the mediation between sound and video is created by an interaction algorithm, built and processed by Processing and Supercollider computer programs. The chapter explores interpretative aspects related to the construction of the narrative and its interaction with the concept of video-art Towards the end, we discuss how the emergence of new sound structures is possible by manipulating symbolic representations between sound, gesture and video. The results presented are adequate for the contingencies of the percussionist musician insofar as they explore new structures and approach problems that transcend the limits of traditional formation. We conclude that the proposed dialogue between scenic gesture and technological mediation not only generates interpretative strategies and solutions, but also promotes continuous thinking about the body in contemporary percussive practice, connection between other artistic languages (theater, dance, cinema), the maintenance and performance of repertoire produced in the late 20th and early 21st centuries, as well as na immersive look into the intense modulation of the contemporary percussion universe.